More Than Shoot‐Em‐Up and Torture Porn: Reflective Appropriation and Meaning‐Making of Violent Media Content. (6th October 2016) - Bartsch, Anne; Mares, Marie‐Louise; Scherr, Sebastian; Kloß, Andrea; Keppeler, Johanna; Posthumus, Lone
Abstract : Media violence research has mainly focused on aggression effects so far. But are audiences' thoughts about violent portrayals actually confined to aggressive fantasies? This study examines more complex thought processes about violent portrayals that involve reflection, meaning‐making, and truth‐seeking about violence as a fact of social reality. We conducted qualitative in‐depth interviews with 39 participants from different backgrounds, including professions at risk for exposure to violence, media professionals, and interviewees from the general population. The interviews revealed three main categories of reflective thoughts about violent media content, including thoughts about (a) the truth value, (b) the life‐world relevance, and (c) the psychological and moral implications of the violence depicted. Participants also discussed unrealistic content features that interfered with meaning‐making.